Holes and channels between the ventricles revisited. (23rd September 2014) - Crucean, Adrian; Brawn, William J.; Spicer, Diane E.; Franklin, Rodney C.; Anderson, Robert H.
Abstract: Background: Although holes, or channels, between the ventricles are the commonest congenital cardiac malformations, there is still no consensus as to how they can best be described and categorised. So as to assess whether it is possible to produce a potentially universally acceptable system, we have analysed the hearts categorised as having ventricular septal defects in a large archive held at Birmingham Children's Hospital. Materials and methods: We analysed all the hearts categorised as having isolated ventricular septal defects, or those associated with aortic coarctation or interruption in the setting of concordant ventriculo-arterial connections, in the archive of autopsied hearts held at Birmingham Children's Hospital, United Kingdom. Results: We found 147 hearts within the archive fulfilling our criterions for inclusion. All could be classified within one of three groups depending on their borders as seen from the right ventricle. To provide full description, however, it was also necessary to take account of the way the defects opened to the right ventricle, and the presence or absence of alignment between the septal components. Conclusions: By combining information on the phenotypic specificity defined on the basis of their borders, the direction of opening into the right ventricle, and the presence or absence of septal malalignment, it proved possible to categorise all hearts examined within the archive of Birmingham Children's Hospital. Our findings have necessitated creation of new numbers within the European Paediatric Cardiac Code.